Habituation-Based Character Education in Islamic Primary Schools: Integrating the 7 Habits Framework within the Merdeka Curriculum - Halimatus Sa’diya; Avidatul Umaidah; Isnainiyah; Subianto; Muhammad Hasan; Ahmad Fauzi (Sustainable, 2026)
Despite widespread adoption of character education programs in Indonesian Islamic primary schools, a persistent gap remains in understanding how global character frameworks can be systematically integrated with local religious curricula to produce holistic student development. While habituation-based approaches have shown promise for fostering discipline and religiosity, existing studies predominantly describe isolated practices without examining the conceptual mechanisms that enable sustainable integration between daily routines and formal religious instruction. This study addresses this lacuna by investigating the implementation of the "7 Habits of Great Children" framework within Islamic Religious Education (PAI) under Indonesia's Merdeka Curriculum. Drawing on qualitative data from classroom observations, in-depth interviews, and document analysis at a purposively selected madrasah, we develop an empirically grounded model demonstrating how structured habituation practices—including communal worship, health routines, and social courtesies—can be theoretically synchronized with PAI learning objectives to create mutually reinforcing character development pathways. Our findings reveal that the integration operates through three conceptual mechanisms: (1) behavioral scaffolding, wherein daily routines provide embodied foundations for abstract religious concepts; (2) contextual bridging, where teachers deliberately connect habituation experiences with PAI content to enhance meaning-making; and (3) environmental synergy, characterized by coordinated reinforcement across school and home settings. The study contributes to character education scholarship by offering a transferable framework for harmonizing universal character principles with culturally situated religious instruction, thereby extending the applicability of habituation theory beyond single-institution implementations. These insights carry implications for curriculum designers and educators seeking to operationalize value-based education within flexible, student-centered learning environments.